Experimental and numerical investigation of the thermal inertia of sugar-beet-pulp/starch based bricks enhanced with phase change materials - Tenpierik, Martin J.; Lachi, Mohammed; Bliard, Christophe; Polidori, Guillaume; Maalouf, Chadi (Construction and Building Materials, 2023)
Due to environmental concerns, bio-based materials are being increasingly investigated and used in buildings. In general, the density of these materials, and thus their thermal inertia, is low. Thermal inertia can be beneficial for reducing the energy use of buildings by damping indoor temperature fluctuations or by reducing and delaying incoming (solar) heat through the façade. This study explores the thermal inertia of regular-sized bricks made of a sugar-beet-pulp/starch mixture (BP/S), and with 17 circular holes inside. The holes were filled either with the BP/S mixture, with air, with a stabilised phase change material (PCM) gel or with a salt-hydrate based PCM. The brick was insulated on all sides but one. Two series of experimental measurements were performed: 1.) a heating film placed at the back (insulated) side of the brick heated the brick until steady-state conditions were reached; 2.) the heated brick was then passively cooled down to ambient temperature by cutting the power to the heating film. Numerical simulations of these experimental measurements were also modelled using the COMSOL Multiphysics® software. In addition, simulations were run to study the thermal inertia of a full brick wall made out of 1 layer and of 4 layers of the BP/S brick with and without PCM, exposed to a combination of a sinusoidal outdoor air temperature fluctuation with an imposed radiation flux on the outdoor surface, representing summer conditions. The results show that the brick in which the holes were filled with phase change material had a slower temperature response and thus higher thermal inertia than the bricks in which the holes were filled with BP/S or with air. The salt-hydrate based PCM with the higher latent heat of fusion led to the slowest temperature response and highest thermal inertia. Furthermore, the calculated simulations could accurately reproduce the experimental measurements. Applying PCM in thick walls (40 cm) made of BP/S bricks however hardly affects the temperature amplitude damping and time delay of the complete wall. The addition of PCM therefore is only effective for thinner walls (10 cm).
Keywords: Beet-pulp; Experiment; Hollowed brick; Phase change material; Simulation; Starch; Thermal inertia